2022
DOI: 10.1136/bmjsem-2021-001258
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma injection for tennis elbow: did it ever work?

Abstract: Platelet-rich plasma (PRP) is a commonly used treatment for tendinopathies such as tennis elbow despite the questionable evidence of its efficacy. A recent Cochrane review suggests that it likely does not provide clinically meaningful benefits in people with tennis elbow. In this viewpoint, we discuss how lack of regulation allowed aggressive marketing and clinical use without normal phases of drug development and approval process or rigorous evidence of benefits. Since several phases of development were bypas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The analysis showed that PRP contains a high concentration of autologous antibodies which may be directly injected into the patient's joint cavity, participating in the immune response and inhibiting the production of inflammatory cells, thus improving the body's inflammatory response. This may be one of the essential reasons why the pain intensity in the PRP group were lower than those in the HA group after treatment [16]. It has been noted that PRP contains a high concentration of active growth factors, which stimulate the differentiation and proliferation of chondrocytes and promote cartilage matrix synthesis [17].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis showed that PRP contains a high concentration of autologous antibodies which may be directly injected into the patient's joint cavity, participating in the immune response and inhibiting the production of inflammatory cells, thus improving the body's inflammatory response. This may be one of the essential reasons why the pain intensity in the PRP group were lower than those in the HA group after treatment [16]. It has been noted that PRP contains a high concentration of active growth factors, which stimulate the differentiation and proliferation of chondrocytes and promote cartilage matrix synthesis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Its effectiveness is confirmed by numerous studies, including many meta-analyses [ 2 , 3 , 4 , 5 , 6 ]. On the other hand, some authors question the evidence of its efficacy [ 7 ]. In the latest network meta-analysis of 25 randomized controlled trials with 2040 patients [ 8 ], the authors concluded that PRP therapy compared to saline control offers significant pain relief, with no significant functional benefits.…”
Section: Introductionmentioning
confidence: 99%